The prevalence of occupational exposure to ergonomic risk factors: A systematic review and meta-analysis from the WHO/ILO Joint Estimates of the Work-related Burden of Disease and Injury. (January 2021) - Hulshof, Carel T.J.; Pega, Frank; Neupane, Subas; van der Molen, Henk F.; Colosio, Claudio; Daams, Joost G.; Descatha, Alexis; Kc, Prakash; Kuijer, Paul P.F.M.; Mandic-Rajcevic, Stefan; Masci, Federica; Morgan, Rebecca L.; et al.
Highlights: WHO and ILO are developing joint estimates of the work-related burden of disease. Systematic review on prevalence of occupational exposure to ergonomic risk factors. Occupational exposure to ergonomic risk factors is highly prevalent. Pooled prevalence of occupational exposure in European region 0.76 (CI 0.69 to 0.84). Main body evidence rated as low quality due to risk of bias and indirectness. Abstract: Background: The World Health Organization (WHO) and the International Labour Organization (ILO) are developing joint estimates of the work-related burden of disease and injury (WHO/ILO Joint Estimates), with contributions from a large network of experts. Evidence from mechanistic and human data suggests that occupational exposure to ergonomic (or physical) risk factors may cause osteoarthritis and other musculoskeletal diseases (excluding rheumatoid arthritis, gout, and back and neck pain). In this paper, we present a systematic review and meta-analysis of the prevalence of occupational exposure to physical ergonomic risk factors for estimating the number of disability-adjusted life years from these diseases that are attributable to exposure to this risk factor, for the development of the WHO/ILO Joint Estimates. Objectives: We aimed to systematically review and meta-analyse estimates of the prevalence of occupational exposure to ergonomic risk factors for osteoarthritis and other musculoskeletal diseases. Data sources: We searched electronic bibliographic databases for potentially relevant records from published and unpublished studies, including Ovid Medline, EMBASE, and CISDOC. We also searched electronic grey literature databases, Internet search engines and organizational websites; hand-searched reference list of previous systematic reviews and included study records; and consulted additional experts. Study eligibility and criteria: We included working-age (≥15 years) workers in the formal and informal economy in any WHO and/or ILO Member State but excluded children (<15 years) and unpaid domestic workers. The exposure was defined as any occupational exposure to one or more of: force exertion, demanding posture, repetitive movement, hand-arm vibration, kneeling or squatting, lifting, and/or climbing. We included all study types with an estimate of the prevalence of occupational exposure to ergonomic risk factors. Study appraisal and synthesis methods: At least two review authors independently screened titles and abstracts against the eligibility criteria at a first stage and full texts of potentially eligible records at a second stage, followed by extraction of data from qualifying studies. We combined prevalence estimates using random-effect meta-analysis. Two or more review authors assessed the risk of bias and the quality of evidence, using the ROB-SPEO tool and QoE-SPEO approach developed specifically for the WHO/ILO Joint Estimates. Results: Five studies (three cross-sectional studies and two cohort studies) met the inclusion criteria, comprising 150, 895 participants (81, 613 females) in 36 countries in two WHO regions (Africa, Europe). The exposure was generally assessed with questionnaire data about self-reported exposure. Estimates of the prevalence of occupational exposure to ergonomic risk factors are presented for all five included studies, disaggregated by country, sex, 5-year age group, industrial sector or occupational group where feasible. The pooled prevalence of any occupational exposure to ergonomic risk factors was 0.76 (95% confidence interval 0.69 to 0.84, 3 studies, 148, 433 participants, 35 countries in the WHO Europe region, I 2 100%, low quality of evidence). Subgroup analyses found no statistically significant differences in exposure by sex but differences by age group, occupation and country. No evidence was found for publication bias. We assessed this body evidence to be of low quality, based on serious concerns for risk of bias due to exposure assessment only being based on self-report and for indirectness due to evidence from two WHO regions only. Conclusions: Our systematic review and meta-analysis found that occupational exposure to ergonomic risk factors is highly prevalent. The current body of evidence is, however, limited, especially by risk of bias and indirectness. Producing estimates for the burden of disease attributable to occupational exposure to ergonomic risk factors appears evidence-based, and the pooled effect estimates presented in this systematic review may perhaps be used as input data for the WHO/ILO Joint Estimates. Protocol identifier: https://doi.org/10.1016/j.envint.2018.09.053 . PROSPERO registration number: CRD42018102631.